Phytochemical analysis and antimicrobial activity of Silybum marianum L. via multi-solvent extraction - Nashaat N. Mahmoud; Mohamed T. Selim (AMB Express)
Abstract Milk thistle (Silybum marianum L.) is an essential medicinal plant belonging to the family Asteraceae. The active ingredient of milk thistle is silymarin, a key component used to treat numerous physical and biological ailments. This study aimed to compare the nutritional composition, total phenolic, flavonoid, and tannin contents, and the antimicrobial activities of S. marianum stems, leaves, and flowers extracted using five different solvents. Phytochemical assays were used to evaluate the total phenolic, flavonoid, and tannin contents in petroleum ether, ethyl acetate, acetone, methanol, and water extracts from different plant parts. The proximate composition showed that the leaves had a higher percentage of moisture (11.53%). In contrast, the flowers showed increased lipid content, carbohydrate, and protein concentration (5.17, 69.86, and 10.03%, respectively), and stems showed elevated ash content (28.67%) compared to leaves and flowers. In S. marianum, the highest yield was obtained from the flowers, while the leaves and stems produced progressively lower amounts, respectively. Among the solvents tested, extraction with water made the largest yield, followed in decreasing order by methanol, acetone, ethyl acetate, and petroleum ether. The findings of the study revealed that alkaloids, tannins, flavonoids, glycosides, steroids, quinones, phenols, anthraquinones, cardiac glycosides, and terpenoids were found by phytochemical analysis of S. marianum in different parts. At the same time, saponins and anthocyanins were completely absent in all parts. On the other hand, coumarins are present in leaves and flowers and are completely lacking in stems. The highest levels of phenol content, tannins, and flavonoids were found in the methanol extract of the flowers (183.12 ± 11.02 mg gallic acid equivalent/g (mg GAE/g), 187.43 ± 15.91 mg quercetin equivalents/g (mg QE/g), and 94.40 ± 16.04 mg TAE/g, respectively). In contrast, the water extract of stems had the lowest amount (5.45 ± 1.32 mg GAE/g, 9.60 ± 1.5 mg QE/g, and 3.27 ± 1.53 mg TAE/g, respectively). Antimicrobial tests revealed the extract's ability to inhibit several Gram-positive bacteria (S. aureus ATCC 6538 and B.subtilis ATCC 6633), Gram-negative bacteria (P. aeruginosa ATCC 9027, S. typhimurium ATCC 14028, E. coli ATCC 11229), and eukaryotic strains such as unicellular fungi (C.albicans ATCC 10231). These results confirm the potential of milk thistle extract as a naturally occurring antimicrobial agent. Graphical abstract